Previous Examination Scores As A Predictor Of Secondary School Students Tendency To Cheat In Chemistry Examination In Lagos State, Nigeria - Aham, Maureen Chikanma; Agu, Ngozi Nwabugo; Metu, Ifeoma Clementina (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
This study investigated previous examination scores as a predictor of secondary school students' tendency to cheat in Chemistry examinations in Lagos State, Nigeria. A correlational survey research design was employed. The study was carried out in secondary schools in Badagry, Lagos State Nigeria. A questionnaire developed by the researchers and validated by experts was used to collect data on students' demographic information, and cheating behaviour. Previous examination scores of the students were collected from the schools’ exams and records unit through the subject teachers. The population of the study was 50,005 Senior Secondary two (SS2) students for 2023/2024 academic session in the eighteen (18) government approved senior secondary schools in Badagry, Lagos State Nigeria. 300 students were selected through stratified random sampling technique. ANOVA and regression analysis were used to analyze the data. The null hypotheses were tested at .05 level of significance. The results showed that previous examination scores have significant predictive power on secondary school students’ tendency to cheat in chemistry and that there is a significant negative correlation between previous examination scores and cheating tendency; students with lower scores were more likely to cheat in chemistry examination. It was recommended among others that educational institutions should provide support for students with low academic achievement, emphasize the importance of academic integrity, and implement effective preventive measures for cheating in exams